Business Specific Online Information Extraction from German Websites - Lee, Yeong Su; Geierhos, Michaela (Computational Linguistics and Intelligent Text Processing: 5th International Conference, CICLing 2004, Seoul, Korea, February 15-21, 2004, Proceedings)
This paper presents a system that uses the domain name of a German business website to locate its information pages (e.g. company profile, contact page, imprint) and then identifies business specific information. We therefore concentrate on the extraction of characteristic vocabulary like company names, addresses, contact details, CEOs, etc. Above all, we interpret the HTML structure of documents and analyze some contextual facts to transform the unstructured web pages into structured forms. Our approach is quite robust in variability of the DOM, upgradeable and keeps data up-to-date. The evaluation experiments show high efficiency of information access to the generated data. Hence, the developed technique is adaptive to non-German websites with slight language-specific modifications, and experimental results on real-life websites confirm the feasibility of the approach.

Guest-editor des Focus On "Corpus Linguistics - Methods and Approaches" - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus-based and corpus-driven approaches: An investigation of the verb do - Mindt, Ilka (Anglistik. International Journal of English Studies)

Corpus Linguistics: a discipline on the move - Mindt, Ilka (Anglistik. International Journal of English Studies)

Assmann, A.: Einführung in die Kulturwissenschaft - Tönnies, Merle (Anglistik. International Journal of English Studies)

Lionel Johnson - Flotmann, Christina (Kindlers Literaturlexikon)

Shelagh Delaney 'A Taste of Honey' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'A Map of the World' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Knuckle' - Tönnies, Merle (Kindlers Literaturlexikon)

David Hare 'Plenty' - Tönnies, Merle (Kindlers Literaturlexikon)

Ann Patricia Jellicoe 'The Knack' - Tönnies, Merle (Kindlers Literaturlexikon)

Stephen Poliakoff 'Strawberry Fields' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Amadeus' - Tönnies, Merle (Kindlers Literaturlexikon)

Peter Shaffer 'Equus' - Tönnies, Merle (Kindlers Literaturlexikon)

George Bernard Shaw 'Mrs Warren's Profession' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Mrs Henry Wood' - Tönnies, Merle (Kindlers Literaturlexikon)

Mary Elisabeth Braddon 'Lady Audley's Secret' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'Lady Windermere's Fan' - Tönnies, Merle (Kindlers Literaturlexikon)

Alan Ayckbourn 'Woman in Mind' - Tönnies, Merle (Kindlers Literaturlexikon)

Wilkie Collins 'The Moonstone' - Tönnies, Merle (Kindlers Literaturlexikon)

Oscar Wilde 'East Lynne' - Tönnies, Merle (Kindlers Literaturlexikon)

Book review: Birgit Neumann, Ansgar Nünning and Bo Pettersson (eds) (2008). Narrative and Identity: Theoretical Approaches and Critical Analyses. Trier: Wissenschaftlicher Verlag Trier - Mildorf, Jarmila (Informationsmittel für Bibliotheken)

Book review: Christian Klein and Matías Martínez. (2009) Wirklichkeitserzählungen: Felder, Formen und Funktionen nicht-literarischen Erzählens. Stuttgart: Metzler - Mildorf, Jarmila (Informationsmittel für Bibliotheken)

iBeCOOL - Extraction d'informations biographiques dans les textes financiers - Geierhos, Michaela; Blanc, Olivier; Bsiri, Sandra (Proceedings of the Lexis and Grammar Conference 2008)
Ce papier présente le contexte linguistique et la modélisation de notre système iBeCOOL (Informations Biographiques Extraites à l’aide de COntextes Observés Linguistiquement) dédié à l’extraction d’informations biographiques dans les textes de la presse financière en langue anglaise. La notion d’événement biographique (tel que la naissance, le mariage, la carrière professionnelle) est caractérisée formellement par un schéma prédicatif à plusieurs arguments dont l’un étant une instance de la classe d’objets <Personne>. Notre approche consiste à décrire ces types de relations à l’aide de grammaires locales etde lexiques terminologiques. Nos résultats montrent que cette approche semble viable et nous poussent à élargir cette étude par l’analyse de nouveaux genres textuels.
Keywords: extraction d’informations biographiques; elations sémantiques; grammaires locales; entités nommées; enrichissement du lexique

ProfilPro: Reconstitution automatique d'un profil professionnel à partir des documents du Web - Geierhos, Michaela; Bsiri, Sandra (Linguistics, Computer Science and Language Processing: Festschrift for Franz Guenthner on the Occasion of His 60th Birthday (Tributes 6))

RELAX - Extraction de relations sémantiques dans les contextes biographiques - Geierhos, Michaela; Blanc, Olivier; Bsiri, Sandra (Traitement Automatique des Langues (TAL))

Appropriateness in Discourse: The adjectives surprised and surprising in monologue and dialogue - Mindt, Ilka (Journal of Pragmatics)

Adjective complementation by that-clauses: the relation between the semantics of adjectives and the verb phrase in the that-clause - Mindt, Ilka (Anglistik. International Journal of English Studies)

Progressives, Patterns, Pedagogy. A corpus-driven approach to English progressive forms, functions, contexts and diadactic - Mindt, Ilka; Römer, Ute (Anglistik. International Journal of English Studies, 19, 2)

Corpus Linguistics 25 Years on. (Language and Computers: Studies in Practical Linguistics 62) - Mindt, Ilka; Facchinetti, Roberta (ICAME Journal, Computers in English Linguistics, 2008)

Learning English - the reading performance of a Japanese 'SUE' (successful user of English) - Rumlich, Dominik (Working papers in Applied Linguistics)

Translating African Traditions and Identities. Black Poetry in Contemporary Britain - Tönnies, Merle (Cultures of Translation)

The Visual Strategies of Nineteenth-Century Melodrama - Tönnies, Merle (Anglistik & Englischunterricht 71)

Kulturelle Bedeutungen und Kontexte der indischen Küche in Großbritannien - Tönnies, Merle (Interkulturelle Mahlzeiten. Kulinarische Begegnungen und Kommunikation in der Literatur)

Caselli, D.: Beckett's Dante - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)

The Frontiers of the Sea - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

A Nose By Any Other Name - Strauß, Sara (Peter Ustinov als Autor – Eine Einführung)

Structuring Job Search via Local Grammars - Bsiri, Sandra; Geierhos, Michaela; Ringlstetter, Christoph (Research in Computing Science)
The standard approach of job search engines disregards the structural aspect of job announcements in the Web. Bag-of-words indexing leads to a high amount of noise. In this paper we describe a method that uses local grammars to transform unstructured Web pages into structured forms. Evaluation experiments show high efficiency of information access to the generated documents.

Female-on-Male Violence: Medical Responses and Popular Imagination - Mildorf, Jarmila (Gender and Interpersonal Violence: Language, Action and Representation)

Kazuo Ishiguro: Never Let Me Go - Mildorf, Jarmila (Novels. Part II)

Thought Presentation and Constructed Dialogue in Oral Storytelling: Limits and Possibilities of a Cross-Disciplinary Narratology - Mildorf, Jarmila (Partial Answers)

Narrative: Knowing, Living, Telling (Partial Answers)

Grammatik der Menschenbezeichner in biographischen Kontexten - Geierhos, Michaela

Informationsextraktion aus Stellenanzeigen im Internet - Bsiri, Sandra; Geierhos, Michaela (LWA 2007: Lernen - Wissen - Adaption, Halle, September 2007, Workshop Proceedings)
Dieser Beitrag beschäftigt sich mit der Informationsextraktion aus Stellenanzeigen im französischsprachigen Web. Ziel dieser Arbeit ist es, unstrukturierte Dokumente in Repräasentationsvektoren anhand lokaler Grammatiken zu transformieren. Auf diese Weise wird es möglich, den Stellenmarkt für Jobsuchmaschinen transparenter zu gestalten, indem nur auf dem Inhalt der Anzeige in Form von Darstellungsvektoren anstatt auf unübersichtlichem Fließtext gesucht werden muss.

The valency of experiential and evaluative adjectives - Mindt, Ilka (Valency. Theoretical, Descriptive and Cognitive Issues)

Constructing an Emblematic Northern Space. The New Brighton Photographs of Martin Parr and Tom Wood - Tönnies, Merle (Spatial Practices 2)

Stierstorfer, K. / L. Volkmann (Hg.): Kulturwissenschaft Interdisziplinär - Tönnies, Merle (Anglistik. International Journal of English Studies)

Introduction to the Study of British Culture - Tönnies, Merle; Voigt, Ulrich

London-Diversity and Myth - Tönnies, Merle (Viewfinder Special. Lese-und Arbeitsbuch für die gymnasiale Oberstufe)

Storying Domestic Violence: Constructions and Stereotypes of Abuse in the Discourse of General Practitioners - Mildorf, Jarmila

Mad Intertextuality: 'Jane Eyre', 'Wide Sargasso Sea', 'After Mrs Rochester' - Mildorf, Jarmila (A Breath of Fresh Eyre: Intertextual and Intermedial Reworkings of 'Jane Eyre')

Book review: Katharina Uhsadel (2005). Antonia Byatts Quartet in der Tradition des Englischen Bildungsromans. Heidelberg: Winter - Mildorf, Jarmila (Anglistik)

Das Paradigma des Pikaresken - The Paradigm of the Picaresque

Thinking Northern: Textures of Identity in the North of England

Distributional data and grammatical structures: The case of so- called subject extraposition - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik 54.2, Special issue on "The scope and Limits of Corpus Linguistics – Empiricism in the Description and Analysis of English)

Forms and Functions of Violence in Contemporary Black British Drama - Tönnies, Merle (Anglistentag 2005)

Foregrounding Boundary Zones. Martin Parr's Photographic (De-)Constructions of Englishness - Tönnies, Merle (Spatial Practices 1)

Percy Mtwa, Mbongeni Ngema and Barney Simon: Woza Albert! (1981) - Tönnies, Merle (Drama II)

New Labour in the New Millenium. A Further Theatricalisation of Politics? - Tönnies, Merle (Passauer Arbeiten zur Literatur-und Kulturwissenschaft)

Radicalising Postmodern Biofictions. British Fictional Autobiography of the Twenty-First Century - Tönnies, Merle (Salzburg Studies in English Literature and Culture)

A Midsummer Night's Dream - Tönnies, Merle (Stauffenburg Handbücher)

Boehmer, E.: Stories of Women, 2005 - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)

Middeke, M.: Die Kunst der gelebten Zeit, 2004 - Tönnies, Merle (Zeitschrift für Anglistik und Amerikanistik)

Kamm, J. / B. Lenz: Großbritannien verstehen, 2004 - Tönnies, Merle (Anglia)

Nünning, V. / A. Nünning (Hg.): Erzähltextanalyse und Gender Studies, 2004 - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)

Sociolinguistic Implications of Narratology: Focalization and ‘Double Deixis’ in Conversational Storytelling - Mildorf, Jarmila (The Travelling Concept of Narrative)

Disenchanting the World, Enchanting the Reader: The Negotiation of Biochemistry in Sinclair Lewis’ 'Arrowsmith' - Mildorf, Jarmila (Magic, Science, Technology, and Literature)

Introduction - Seeber, Hans Ulrich; Mildorf, Jarmila; Windisch, Martin (Magic, Science, Technology, and Literature)

Book review: Alan Palmer (2004). Fictional Minds. Lincoln: University of Nebraska Press - Mildorf, Jarmila (Anglia)

Learner English: Ein Überblick über vorhandene Korpora und mögliche Forschungsansätze - Mindt, Ilka (Korpuslinguistik Deutsch: synchron – diachron – kontrastiv. Würzburger Kolloquium 2003)

Corpora in Applied Linguistics - Mindt, Ilka; Hunston, Susan (ICAME Journal 29, Computers in English Linguistics)

A Student's Introduction to English Grammar - Mindt, Ilka; Huddleston, Rodney; Pullum, Geoffrey K. (Zeitschrift für Anglistik und Amerikanisitk. A Quarterly of Language, Literature and Culture. Heft 2, 2)

Lexikalische Dynamik: Kognitiv-linguistische Untersuchungen am englischen Computerwortschatz - Mindt, Ilka; Bründl, Monika Elisabeth (Anglistik. Mitteilungen des Deutschen Anglistenverbandes)

Courttia Newland's Theatre Work. On the Occasion of B is for Black (Oval House Theatre, London, 1-18 October 2003 - Tönnies, Merle (Hard Times)

'Serious' Science vs. 'Light' Entertainment? Femininity Concepts in Nineteenth-Century British Medical Discourse and Popular Fiction - Tönnies, Merle (Unmapped Countries: Biological Visions in Nineteenth-Century Literature and Culture)

A New Self-Conscious Turn at the Turn of the Centruy? - Tönnies, Merle (anglistik & englischunterricht)

Das viktorianische Theater als Populärkultur - Tönnies, Merle (Eine Kulturgeschichte der englischen Literatur: Von der Renaissance bis zur Gegenwart)

Hooper, B.: Voices in the Heart. Postcolonialism and Identity in Hong Kong Literature, 2003 - Tönnies, Merle (Anglistik)

Words That Strike and Words That Comfort: Discursive Dynamics of Verbal Abuse in Roddy Doyle’s "The Woman Who Walked Into Doors" - Mildorf, Jarmila (Journal of Gender Studies)

New Britain as Consumer Country and Commodity - Tönnies, Merle (Journal for the Study of British Cultures)

Mergenthal, S.: A Fast-Forward Version of England, 2003 - Tönnies, Merle (Anglia)

Narrativising the Body: Fragmentation and Unification in Jed Mercurio’s 'Bodies' - Mildorf, Jarmila (Interdisciplinary Perspectives on Health, Illness and Disease)

Narratives of Domestic Violence Cases: GPs Defining their Professional Role - Mildorf, Jarmila (Making Sense of Health, Illness and Disease)

Book review: Vera and Ansgar Nünning (eds) (2002). Erzähltheorie transgenerisch, intermedial, interdisziplinär. Trier: WVT. / Ansgar and Vera Nünning (eds) (2002). Neue Ansätze in der Erzähltheorie. Trier: WVT - Mildorf, Jarmila (Narrative Inquiry)

Is I think a Discourse Marker - Mindt, Ilka (Anglistentag 2002 Bayreuth. Proceedings of the Conference of the German Association of University Teachers of English, Volume XXIV)

Tagungsbericht über das Internationale Kolloquium Korpuslinguistik Deutsch: synchron – diachron – kontrastiv (klde 2003) - Mindt, Ilka (Zeitschrift für Deutsche Philologie 122)

Form and function of parasyntactic presentation structures. A corpus-based study of talk units in spoken English - Mindt, Ilka; Mukherjee, Joybrato (ICAME Journal, 27, Computers in English Linguistics)

Peter Brook's Glückliche Tage - Tönnies, Merle (The Beckett Circle)

'New Lingo - New Theatre'? - Tönnies, Merle (anglistik & englischunterricht)

The 'Postcolonial University Novel' in Britain. - Tönnies, Merle (Xenophobic Memories: Otherness in Postcolonial Constructions of the Past)

Making Play-texts Live: Teaching Drama as Experience - Tönnies, Merle; Annette, Pankratz; Alyce, von Rothkirch; Kathleen, Stark (Global Challenges and Regional Responses in Contemporary Drama in English)

Sager, P.: Oxford & Cambridge. Eine Kulturgeschichte - Tönnies, Merle (Journal for the Study of British Cultures)

Veit, C.: Ich-Konzept und Körper in Becketts dualen Konstruktionen, 2002 - Tönnies, Merle (The Beckett Circle)

Logan, T.: The Victorian Parlour, 2001 - Tönnies, Merle (Anglia)

Keipert, H.: Pope, Popovskij und die Popen, 2001 - Tönnies, Merle (Archiv für das Studium der neueren Sprachen und Literaturen)

Heinemann, P.: Potenzierte Subjekte – Potenzierte Fiktionen. Ich-Figurationen und ästhetische Konstruktion bei Jean Paul und Samuel Beckett, 2001 - Tönnies, Merle (The Beckett Circle)

Beckett, S.: Dante und der Hummer. Gesammelte Prosa, 2000 - Tönnies, Merle (The Beckett Circle)

Functions of intonation in sentences and texts - Mindt, Ilka (New Frontiers of Corpus Research. Papers from the Twenty First International Conference on English Language Research on Computerized Corpora)

Emerging English Modals: A Corpus-Based Study of Grammaticalization - Mindt, Ilka; Krug, Manfred (Journal of English Linguistics, Volume 30, Number 3)

Good/Bad Girls and their Fathers - Tönnies, Merle (Journal for the Study of British Cultures)